HPLC analysis of carotenoids in four varieties of Calendula officinalis L. flowers - Pintea, Adela (Acta Biologica Szegediensis, 2003)
Calendula officinalis L. is a medicinal plant that accumulates large amounts of carotenoids in its inflorescences. The yellow-to-orange colour of inflorescences is mostly due to carotenoids and the shade is dependent on pigments content and profile.We investigated the carotenoid content and profile in four selected varieties of Calendula: Double Esterel Orange, Radio Extra Selected, Bonbon Abricot and Double Esterel Jaune. The total carotenoid content was evaluated spectrophotometrically and pigments were separated using chromato-graphic methods (CC, TLC, HPLC). An HPLC gradient system with a Nucleosil C18 column and a Waters PDA detector was used for separation and identification of carotenoids. The carotenoid content was higher in orange varieties: 276 mg/100 g fresh flowers for Double Esterel Orange and 111 mg/100 g fresh flowers for Radio variety. All varieties contain the same pigments but there are significant differences for the ratio between individual pigments. Orange varieties contain higher amounts of hydrocarbons: 44.5% of total carotenoid in Double Esterel Orange; while yellow varieties contain mostly oxygenated derivatives: 97% of total carotenoids in Double Esterel Jaune. The main pigments identified were: flavoxanthin, lutein, rubixanthin, b-carotene, b-carotene and lycopene. The cultivation of orange varieties is recommended especially when the pharmacological products for skin protection are envisaged.